Classification of methods to make final effort in javelin throw - Abakumova, M. V.; Chermit, K. D.; Zabolotniy, A. G. (Theory and Practice of Physical Culture, 2020)
Objective of the present study was to identify kinematic characteristics of the technique of throwing auxiliary projectile.